Description of Anxiety and Stress Levels of Chronic Kidney Failure Patients in the Hemodialysis Room of Dr. Soedarso Hospital - Ardila, Marsyah; Pramana, Yoga; Sulistyawati, Ririn Afrian; Mita; Lekatompessy, Roland (Tanjungpura Journal of Nursing Practice and Education, 2026)
The purpose of this study is to describe the levels of anxiety and stress among patients with chronic kidney failure undergoing hemodialysis at Dr. Soedarso General Hospital. This research is a quantitative study using a descriptive, cross-sectional design. The sampling technique used was non-probability purposive sampling, with a total sample of 129 respondents. Data were collected using the Zung Self-Rating Anxiety Scale (ZSAS) to measure anxiety and the Perceived Stress Scale-10 (PSS-10) to measure stress among patients in the hemodialysis unit. The results showed that 120 respondents (93%) had normal anxiety levels and 9 respondents (7%) had mild anxiety, while 74 respondents (57.4%) experienced mild stress, 53 respondents (41.1%) moderate stress, and 2 respondents (1.6%) severe stress. Anxiety and stress are real problems experienced by CKD patients undergoing hemodialysis; therefore, healthcare professionals need to pay special attention to these issues in order to help patients adapt to the chronic illness they are facing.